2021
DOI: 10.1097/olq.0000000000001432
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intracranial Vessel Wall Magnetic Resonance Imaging to Detect a Presumptive Syphilitic Brain Aneurysm

Abstract: Syphilitic intracranial aneurysm is a rare presentation of meningovascular syphilis in developed countries. In this case report, we discuss the utilization of the intracranial vessel wall magnetic resonance imaging in the management of a patient with a rare fusiform brain aneurysm, positive syphilis serologies, and inconclusive cerebrospinal fluid findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…VZV, HSV, HIV, SARS-CoV 2) Own data a ; Lersy et al [ 45 ]; Mossa-Basha et al [ 34 ]; Cheng-Ching et al [ 24 ], Küker et al [ 22 ] Basal meningitis caused by tuberculosis or fungal infections Lu et al [ 46 ]; Lopes et al [ 47 ] Bacterial infection (e.g. borreliosis, lues) Askar et al [ 48 ]; Bäuerle et al [ 49 ]; Kurian et al [ 50 ]; Lebas et al [ 51 ] Radiation-induced vasculopathy Li et al [ 52 ] Noninflammatory vasculopathies RCVS Chen et al [ 32 ];Mossa-Basha et al [ 34 ]; Obusez et al [ 25 ] Atherosclerosis Mossa-Basha et al [ 34 ]; Mossa-Basha et al [ 33 ]; Skarpathiotakis et al [ 35 ]; Lou et al [ 53 ] CADASIL Goldstein et al [ 54 ] Moyamoya angiopathy Wang et al [ 36 ]; Mossa-Basha et al [ 33 ]; Ryoo et al [ 55 ]; Kim et al [ 56 ] Metabolic diseases Fabry disease Kong et al [ 57 ] Malignant diseases Vascular lymphoma Schaafsma et al [ 58 ] a Vessel wall contrast enhancement reported in this study …”
Section: Discussionmentioning
confidence: 99%
“…VZV, HSV, HIV, SARS-CoV 2) Own data a ; Lersy et al [ 45 ]; Mossa-Basha et al [ 34 ]; Cheng-Ching et al [ 24 ], Küker et al [ 22 ] Basal meningitis caused by tuberculosis or fungal infections Lu et al [ 46 ]; Lopes et al [ 47 ] Bacterial infection (e.g. borreliosis, lues) Askar et al [ 48 ]; Bäuerle et al [ 49 ]; Kurian et al [ 50 ]; Lebas et al [ 51 ] Radiation-induced vasculopathy Li et al [ 52 ] Noninflammatory vasculopathies RCVS Chen et al [ 32 ];Mossa-Basha et al [ 34 ]; Obusez et al [ 25 ] Atherosclerosis Mossa-Basha et al [ 34 ]; Mossa-Basha et al [ 33 ]; Skarpathiotakis et al [ 35 ]; Lou et al [ 53 ] CADASIL Goldstein et al [ 54 ] Moyamoya angiopathy Wang et al [ 36 ]; Mossa-Basha et al [ 33 ]; Ryoo et al [ 55 ]; Kim et al [ 56 ] Metabolic diseases Fabry disease Kong et al [ 57 ] Malignant diseases Vascular lymphoma Schaafsma et al [ 58 ] a Vessel wall contrast enhancement reported in this study …”
Section: Discussionmentioning
confidence: 99%